A New Market for Pet Food in China: Online Consumer Preferences and Consumption. Issue 6 (2nd November 2021) - Xiao, Yunyang; Wang, H. Holly; Li, Jun
Abstract: The pet industry has grown tremendously in China, and pet food is a major product in the market. Although characteristics of pet food are important considerations for veterinarians and consumers, there has yet to be a holistic consumer study for Chinese pet food shopping behaviors. This study focuses on consumer stated preferences of online pet food and factors affecting their actual purchasing behavior. We have conducted a survey and explored factors affecting both consumers' stated attribute preferences and factors affecting their consumption quantities. A total of 220 valid samples were collected online from pet owners with online shopping experiences in 2019. Our results reveal that younger, urban, higher educated, and married consumers with families tend to use more online channels to buy pet food. They care more about brand, ingredients, and retailer reputation, but not so much about imported products. We find little significant statistic difference between consumers' online and offline shopping perspectives. This paper quantitatively investigates consumer pet food shopping behaviors, discovers recent trends in this line of research, and provides insight into the industry for future developing demand.